Investigación acerca del tratamiento de la información sobre la regeneración ambiental de la bahía de Portmán (La Unión-Murcia) - García Belchí, Manuela (Documentación de las Ciencias de la Información, 2007)
Study of nature and channels used to inform society on the measures taken for environmental regeneration, counteracting mining pollution at Portman Bay in Murcia province; results from research on the subject, outlining various sources and methodology used for processing print documents (press media) and general conclusions drawn from the study.